Integral diagnosis of occupational health and safety management in Colombian construction companies (2017)
Given the particular characteristics of the construction sector, its rate of accidents and contracted illnesses is high. Therefore, construction companies seek to protect the health of their workers through the design and implementation of occupational health and safety management systems (OHSMS). This paper presents the results of a study that aimed to perform a comprehensive diagnosis of the implementation of the requirements of the Colombian Technical Standard (Norma Técnica Colombiana, NTC-OHSAS 18001) in Colombian construction companies through a SWOT analysis. A survey of 25 questions to industry professionals in 5 capital cities was used for data collection. The survey was conducted in two ways: virtually with the help of the Google Docs platform and directly through written forms. A total of 209 questionnaires with valid answers were received. The findings show that a lack of commitment and a lack of knowledge about safety are the main weaknesses. On the other hand, the existence of occupational health and safety (OHS) staffand the promotion of OHS by Occupational Risk Administrators (ORA) are the main strengths. From this data, alternatives for improving OHS are proposed, such as greater investment in builders, increasing organisational culture, and adequate monitoring by the State. © Penerbit Universiti Sains Malaysia, 2017.